Probing the Reactivity of Functionalized Surfaces by Porphyrin Metalation. Issue 5 (20th April 2016) - Nowakowski, Jan; Nowakowska, Sylwia; Srivastava, Gitika; Baljozovic, Milos; Girovsky, Jan; Ballav, Nirmalya; Jung, Thomas A.
Abstract: The presence of N‐ and Cl‐induced superstructures is shown to drastically alter the physicochemical properties of the Cu(001) substrate. We present coherent evidence that N‐ and Cl‐c(2x2) superstructures on Cu(001) decisively impact the metalation reaction of 5, 10, 15, 20‐tetraphenylporphyrin (2HTPP) as well as the on‐surface diffusion and assembly of this molecule. The N superstructure facilitates the metalation reaction and self‐assembled molecular domains of CuTPP are formed at room temperature (RT). In contrast, the Cl superstructure completely inhibits the self‐metalation reaction requiring metal atoms to be deposited from the top and causes 2HTPP to assemble into small clusters. A spectro‐microscopy correlation approach combining X‐ray Photoelectron Spectroscopy (XPS), Ultraviolet Photoelectron Spectroscopy (UPS), Low Energy Electron Diffraction (LEED) and Scanning Tunneling Microscopy (STM) has been utilized in this study. Abstract : The on‐surface metalation reaction is used as a probe to detect reactive metal atoms on functionalized surfaces. Two different Cu(100) substrate modifications induce a drastically different response in molecular assembly as well as in the studied on‐surface reaction: the N superstructure facilitates metalation, while the Cl superstructure inhibits it completely, requiring metal atoms to be deposited from the top.